2020
DOI: 10.1155/2020/3251956
|View full text |Cite
|
Sign up to set email alerts
|

Altered Bioavailability of Nitric Oxide and L-Arginine Is a Key Determinant of Endothelial Dysfunction in Preeclampsia

Abstract: Background. Preeclampsia is a major cause of maternal and neonatal morbidity and mortality in sub-Saharan Africa. Evidence indicates that endothelial dysfunction is central to the pathogenesis of preeclampsia. This study assessed the level of the components of the arginine-nitric oxide pathway to evaluate endothelial dysfunction in normotensive pregnancies and pregnancies complicated with preeclampsia. Methods. This case-control study was conducted among pregnant women who visited Comboni Hospital from January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…In this sense, some studies have found an inverse correlation between NO levels and levels of sFlt-1 and sEng in women with PE, thereby suggesting that somehow anti-angiogenic factors may inhibit the production of NO [158]. The diminished NO production is also potentially related to the reduced bioavailability of its precursor, L-arginine, both being observed in women with PE [159]. These alterations may promote changes in the renal and cardiac microvasculature as well as a reduction in the number of fetal nephrons in vivo, which can possibly also occur in humans [160].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In this sense, some studies have found an inverse correlation between NO levels and levels of sFlt-1 and sEng in women with PE, thereby suggesting that somehow anti-angiogenic factors may inhibit the production of NO [158]. The diminished NO production is also potentially related to the reduced bioavailability of its precursor, L-arginine, both being observed in women with PE [159]. These alterations may promote changes in the renal and cardiac microvasculature as well as a reduction in the number of fetal nephrons in vivo, which can possibly also occur in humans [160].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…However DDAH is also targeted and inhibited by ROS [ 179 ]. It is suggested that reduced levels of l -arginine, rather than increased ADMA levels, may play a role in PE [ [180] , [181] , [182] ].…”
Section: Placental Enos Dysfunction and Oxidative Stress In Pe Pathogmentioning
confidence: 99%
“…Antepartum PE is largely understood as a disorder arising from an abnormal placentation. It is thought that impaired placentation leads to the release of abnormal levels of some angiogenic, anti-angiogenic and vasoactive molecules into maternal circulation, triggering maternal endothelial dysfunction, systemic inflammation, elevated blood pressure and proteinuria 7 , 8 . Altered maternal serum levels of these molecules have been suggested as potential biomarkers of antepartum PE 7 9 while elevated serum levels of soluble fms-like tyrosine kinase 1 (sFlt-1) and decreased serum levels of placental growth factor (PlGF), as well as elevated sFlt-1: PlGF, have been validated as biomarkers of this disease 10 13 .…”
Section: Introductionmentioning
confidence: 99%